The Plea of Illegality as a Pillar of the Incidental Review - (:unkn) unknown (KLUWER LAW INT, 2019)
The plea of illegality as a limb of incidental review alongside the preliminary ruling procedure is examined in light of its raison d'etre, nature, ratione materiae and personae scope and its interrelated characteristics with other remedies and procedures in the EU judicial system. This article considers the origin of anomalies in the inconsistent case law reaching different conclusions with regard to standing of different applicants on a selective basis in the transposition of national procedure of exception d'illegalite into the Rome Treaty with a general wording. It is argued that the broad interpretation of ratione personae scope of the procedure on the basis of the wording of Article 277 TFEU requires, in parallel, relaxation of the strict application of the admissibility requirements towards individual applications especially where irregularities might become apparent after the concrete application of the general act in order to prevent from carrying privileged or non-privileged status of applicants under the action for annulment to the plea of illegality.
Keywords: Plea of Illegality; Incidental Review; Acts of General Application; Legal Certainty v Legality; Complementary or Alternative Remedy